ISOLATION AND CHARACTERIZATION OF HYDROCARBON DEGRADING BACTERIA IN CRUDE OIL POLLUTED SOIL IN THE NIGER DELTA - MANSI, EGBO W.; AKARANTA, PROF ONYEWUCHI; ABU, PROF GIDEON (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Bioremediation as pollution remediation technique takes advantage of the ability of somemicroorganisms to degrade organic matter in the environment. Bacteria are important group ofmicroorganism that plays key role in the bioremediation process. Bacteria are ubiquitousorganisms that inhabit soil water and air matrices. In this study, some hydrocarbon degradingbacteria have been isolated and identified by morphological and biochemical methods.. Eightdifferent hydrocarbon degrading bacteria were isolated from crude polluted soil collected fromoil spill site in Ikarama community in Yenagoa Local Government Area of Bayelsa State in theNiger Delta. The total population of heterotrophic bacterium enumerated per gram of eachsoil sample are 1.42x107, 1.7x107 and 3.1x108 for location 1,2 and 3 respectively Whilepopulation of total hydrocarbon degrading bacteria enumerated are 4.2x106,: 3.7x106 and1.43x106for location 1, 2 and 3 respectively. This population of hydrocarbon degradingbacteria in the soil is enough to initiate natural biodegradation of crude oil pollutant. Withthe right environmental conditions for the bacteria, bioremediation can be effectivelydeployed to remediate the spilled area.